2019
DOI: 10.1111/exsy.12451
|View full text |Cite
|
Sign up to set email alerts
|

Ranking manufacturing processes from the quality management perspective in the automotive industry

Abstract: The aim of this study is to propose a fuzzy decision‐making model to rank manufacturing processes from the quality management perspective in the automotive industry. This paper proposes a model for improving quality management through the assessment and ranking of manufacturing subprocesses with respect to key performance indicators (KPIs). The developed model, supported with the fuzzy extended ELECTRE III, allows for the determination of subprocesses' rank. An illustrative example indicates that the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It is assumed that DMs may assess the relative importance of criteria in the direct manner. In the literature, the fuzzy rating aggregation of DMs into unique assessment is based on aggregation operators in many cases (Nestic et al, 2019). In this way, the treated criteria are considered independently.…”
Section: Criteria Weightsmentioning
confidence: 99%
“…It is assumed that DMs may assess the relative importance of criteria in the direct manner. In the literature, the fuzzy rating aggregation of DMs into unique assessment is based on aggregation operators in many cases (Nestic et al, 2019). In this way, the treated criteria are considered independently.…”
Section: Criteria Weightsmentioning
confidence: 99%
“…Fuzzy decision-making model justification (ELECTRE III) was employed to rank the manufacturing processes involved in the automobile industry in view of quality management perspective. 20 The authors reported that the proposed methodology can also be useful in everyday business operations as a total quality management asset. CES selector software was employed to select the most suitable PCM from more than 300 PCMs having a temperature range from −50 C to 150 C for building applications.…”
Section: Introductionmentioning
confidence: 98%
“…Fuzzy decision‐making model justification (ELECTRE III) was employed to rank the manufacturing processes involved in the automobile industry in view of quality management perspective 20 . The authors reported that the proposed methodology can also be useful in everyday business operations as a total quality management asset.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the basic task of the reliability manager is how to choose a set of quality methods whose application of the considered problem can be effectively solved in the shortest possible time. Many authors suggest that the choice of quality methods should be based on the priority of failures [8][9][10][11]. Experiences of best practice show that decision makers (DMs), when choosing quality methods, respect many criteria besides the priority of failures.…”
Section: Introductionmentioning
confidence: 99%